2017
DOI: 10.1038/s41598-017-03720-x
|View full text |Cite
|
Sign up to set email alerts
|

Proboscis infection route of Beauveria bassiana triggers early death of Anopheles mosquito

Abstract: Entomopathogenic fungi are known to control vector mosquito populations. Thus, understanding the infection dynamics of entomopathogenic fungi is crucial for the effective control of insect pests such as mosquitoes. We investigated the dynamics of Beauveria bassiana s.l. 60-2 infection of Anopheles stephensi by exposing the mosquito to fungus-impregnated filter paper through two infection routes and then comparing the mortality and extent of infection. Fungal development was observed after using this inoculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Beauveria bassiana is one of the most studied species and its isolates have been commercialized worldwide as mycoinsecticides 7 , 8 . This species is composed of diverse isolates able to exploit a wide range of environments and has a broad range of arthropod hosts 9 11 . Although many B. bassiana -based mycoinsecticides have been produced worldwide, they are still underused because of industrialization conflicts concerning how the isolates are different.…”
Section: Introductionmentioning
confidence: 99%
“…Beauveria bassiana is one of the most studied species and its isolates have been commercialized worldwide as mycoinsecticides 7 , 8 . This species is composed of diverse isolates able to exploit a wide range of environments and has a broad range of arthropod hosts 9 11 . Although many B. bassiana -based mycoinsecticides have been produced worldwide, they are still underused because of industrialization conflicts concerning how the isolates are different.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the larvae exposed to the action of nymphs (predatory role) were much more vulnerable, in the adult stage, to the action of B. bassiana spores [89]. Ishii et al [90] demonstrated the adulticidal action of B. bassiana conidia against An. stephensi mosquitoes.…”
Section: Introductionmentioning
confidence: 99%
“…stephensi mosquitoes. Seven days after exposure, the insect's body was completely invaded by hyphae [90]. Oomycetes Lagenidium giganteum, Aphanomyces laevis, Couchia spp., Crypticola spp., Leptolegnia caudata and Pythium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Sorokin (Hypocreales: Clavipitaceae), an opportunistic fungal entomopathogen that has shown promise for the control of larvae and adults of the African malaria mosquito, Anopheles gambiae Giles (Diptera: Culicidae) in laboratory and semi-field environments (Bukhari et al 2011, Fawrou et al 2013, Lovett et al 2019). Similarly, the ascomycetous fungus, Beauveria bassiana (Balsamo) Vuillemin (Hypocreales:Cordycipitaceae), is an entomopathogenic fungus that has a wide host range, including larvae and adults of several mosquito species (Clark et al 1967, 1968, Miranpuri and Khachatourians 1991, Geetha and Balaraman 1999, Bukhari et al 2010, 2011, Darbro et al 2012, Ishii et al 2017, Benzina et al 2018). B. bassiana infects mosquito larvae by attaching to the larval body at the head and perispiracular lobes of the siphon (Clark et al 1968, Miranpuri and Khachatourians 1991) and through ingestion of fungal spores (Miranpuri and Khachatourians 1990).…”
Section: Introductionmentioning
confidence: 99%